2004
DOI: 10.1254/jphs.sc0030119
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Benidipine and Diltiazem in a Rat Model of Experimental Angina

Abstract: Abstract. We examined the combined effects of the calcium channel blockers 1,4-dihydropyridine (benidipine) and benzothiazepine (diltiazem) on vasopressin-induced myocardial ischemia in anesthetized rats, an experimental model of angina. Benidipine (3, 10 mg / kg, i.v.) and diltiazem (300, 1000 m g / kg, i.v.) caused dose-related inhibition of vasopressin-induced S-wave depression, an index of myocardial ischemia. Co-administration of low doses of benidipine (3 m g / kg) and diltiazem (300 mg / kg) almost comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Combination effects of benidipine and diltiazem for the treatment of angina have also been reported in rats (90). Benidipine shows more vascular selectivity and less negative inotropic activity compared to diltiazem, and induces a longer-lasting increase in coronary blood flow (96,97).…”
Section: Cardioprotective Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination effects of benidipine and diltiazem for the treatment of angina have also been reported in rats (90). Benidipine shows more vascular selectivity and less negative inotropic activity compared to diltiazem, and induces a longer-lasting increase in coronary blood flow (96,97).…”
Section: Cardioprotective Effectsmentioning
confidence: 99%
“…Potent antianginal effects of benidipine have been shown in various models of angina (90,91,96). Combination effects of benidipine and diltiazem for the treatment of angina have also been reported in rats (90).…”
Section: Cardioprotective Effectsmentioning
confidence: 99%
“…Recently, we reported that the combination of diltiazem and benidipine exerted potent antianginal effects in the vasopressin-induced angina rat model. 5) To elucidate the beneficial effects of the combination of benidipine and diltiazem in angina, the present study focused on CF and DP in anesthetized dogs. The results of the present study demonstrates that the combination of benidipine and diltiazem significantly decreased DP in comparison to benidipine alone, and significantly and continuously increased CF.…”
Section: Discussionmentioning
confidence: 99%
“…We reported recently that the combination of diltiazem and benidipine exerted potent antianginal effects in the vasopressin-induced angina rat model. 5) However, there have been no published reports concerning the hemodynamic profile of the combination of diltiazem and benidipine. Therefore, in the present study we examined the hemodynamic effects of diltiazem, benidipine, and the combination of these drugs in anesthetized dogs.…”
mentioning
confidence: 99%
See 1 more Smart Citation